Management of Child Friendly Schools To Develop Students Psychological Well Being - Ulfah, Ulfah; Hanafiah, Hanafiah; Cepi Barlian, Ujang; Koswara, Nandang (International Journal of Education and Digital Learning (IJEDL), 2022)
The background of this research is that the number of violence is increasing, the violence that occurs is not only in the physical but psychological or psychological aspects, and the number of violence that occurs in schools is in the top 3 ranking of violence that occurs in families and alternative care settings. This research is qualitative research with a case study method. The results of this study indicate that 1) Child-friendly school planning is carried out based on the program and there is an obligation to participate in the Adiwiyata School program, 2) Mechanisms for division of tasks and management functions for child-friendly schools are regulated based on a school principal's decision letter, 3) Supervision of child-friendly schools has been carried out by schools since students after attending MPLS, in learning, participation in extracurricular activities and the interactions they build, especially with teachers, friends and their parents, 4) Organizing child-friendly schools is guided by rules, which is one of the components used as a benchmark for achieving friendly schools children is in terms of learning, 5) Obstacles faced related to child-friendly school planning in general there is still a lack of facilities to support child-friendly school programs, especially interesting places to develop their talents and interests, and 6) The solution is to provide learning facilities ber indoor and outdoor facilities that can support the implementation of the learning process.